A Predictive Formula for Portal Venous Pressure Prior to Liver Resection Using Directly Measured Values. Issue 2 (7th February 2020) - Hidaka, Masaaki; Eguchi, Susumu; Hara, Takanobu; Soyama, Akihiko; Okada, Satomi; Hamada, Takashi; Ono, Shinichiro; Adachi, Tomohiko; Kanetaka, Kengo; Takatsuki, Mitsuhisa
ABSTRACT: Purpose : Despite refinements in surgical techniques for liver resection, evaluation of hepatic reserve disparity remains one of the most common problems in liver surgery, especially for hepatic malignancies such as hepatocellular carcinoma (HCC). Portal venous pressure (PVP) is regarded one of the important factors in selecting treatment strategy, although its measurement can be invasive and complex. Methods : To establish a formula for calculating PVP preoperatively, intraoperative directly measured PVP was used in 177 patients with preoperative factors and liver function tests such as age, sex, virus status, platelet count, prothrombin time, albumin, total bilirubin, alanine aminotransferase (ALT), Child–Pugh grade, liver damage defined by the Liver Cancer Study Group of Japan, indocyanine green retention rate at 15 min (ICG-R15), and the aspartate transaminase (AST)-platelet ratio index (APRI). Results : Although 90% of the patients were classified as Child-Pugh A, median direct PVP was 16.5 cm H2 O (5.5–37.0) and the percentage of PVP greater than 20 cm H2 O was 27.1%, reflecting portal hypertension due to liver damage. After multiple regression analysis, the formula PVP (cmH2 O) = EXP[2.606 + 0.01 × (ICG-R15) + 0.015 × APRI] was established from the measured data. Conclusion : Considering its simplicity of use, we have adopted this formula for predicting PVP in determining treatment strategy for HCC and other hepatic malignancies.